Sejarah Penulisan dan Pembukuan Al-Qur’an - Anisa Maulidya; Mhd. Armawi Fauzi (Tarbiatuna: Journal of Islamic Education Studies, 2023)
Al-Qur'an is an Islamic holy book that was given to Nabi Muhammad by Allah as the primary guide for his life. When the Qur'an was reintroduced, the number of people who could read and write it was limited, and the medium of writing was also limited, so the Qur'an was only read by the people.. Then, when did the completion of the Qur'an and its publication become the Kitab that Muslims today use? The purpose of this research is to analyze the history of the Quran and its publication. The current study makes use of a quantitative methodology for research done in libraries as well as other types of quantitative research. Data for the study was compiled from books and journals related to the Qur'an. a data collection technique involving the collection of literature or raw materials related to research. The results of this study show that there are three periods in the history of the Qur'an, namely the periods of Rasulullah, Abu Bakr, and Utsman, during which improvements were made to make it easier for Muslims to read the Qur'an. Keyword: History, Qur’anic Writing, Qur’anic Publication.